Supervisor Sponsorship, Soft Skills, Emotional Intelligence, and Growth Mindset: As an Effort to Predict Career Success in Work Experience - Siti Nur Aisah; Rosida; Rahma Wardani (KASTA : Jurnal Ilmu Sosial, Agama, Budaya dan Terapan, 2026)
Predicting career success is a strategic effort to understand and direct an employee's professional journey. Supervisor sponsorship, soft skills, emotional intelligence, and growth mindset are used to predict employee success after 3 years of work experience in the same position and company, so that careers become more planned, measurable, and in line with potential and long-term goals. Supervisor sponsorship was chosen because it paves the way for employee careers. Soft skills and emotional intelligence were chosen because they can strengthen performance rather than success, while growth mindset was chosen because it can be a tool in maintaining the sustainability of individual development in thinking patterns. The approach used in this study was quantitative with a sample population of 150 coal employees in Banjarmasin, South Kalimantan with 3 years of work experience in the same position and company. The method used in this study was purposive sampling, data were analyzed using Structural Equation Modeling (SEM) with the LISREL program. The results showed that supervisor sponsorship, soft skills, emotional intelligence, and growth mindset positively predicted career success for coal employees after 3 years of work experience in the same position and company in Banjarmasin, South Kalimantan. The four variables support in predicting the success of employees who have worked in the same position and company for 3 years in the same position and company in understanding and directing an employee's professional journey.